Medium- And Long-term Power Curve Division Mechanism Based on Energy Block Segmentation. Issue 1 (January 2021) - Guo, Jinhui; Yuan, Yunyun; Liang, Chao; Zhou, Yv; Liu, Dunnan; Qin, Guangyu; Wang, Lingxiang
Abstract: With the development of electric power system reform, it is very important to design the medium- and long-term curve division mechanism for electric power in China. The essence of power supply is "continuous" energy block supply. The two sides of supply and demand take the power block as the interactive unit agreement to deal with electricity. The model of medium- and long-term curve division based on energy block can reflect the abundance of electric power, be beneficial to the stable and reliable supply of electric power and effectively reduce the loss of auxiliary service. Based on the development of new power systems at home and abroad, this paper designs the power curve division mechanism based on energy blocks, and takes Qinghai Province as an example to study its medium - and long-term power curve division mechanism with high proportion of renewable energy.